War impacts on youth business groups in Tigray - Stein Terje Holden; Mesfin Tilahun; Tsegabirhan Gebremedhin (Norwegian University of Life Sciences (NMBU), Centre for Land Tenure Studies (CLTS), 2024)
Our study investigates the impact of the November 2020 to November 2022 Tigray war on youth groups and their members based on survey data from 281 youth group leaders and 2528 youth group members in five districts in the Tigray region of northern Ethiopia. The data was collected from August to December 2023 using standardized survey instruments. Our data is complemented with baseline data that indicate the pre-war situation for the same groups and members in 2019. This gives us unique data to compare the situation of a large sample of business groups and members one year before the war started with that one year after the war ended. Our results show that the war has had devastating effects on the youth groups and their members in terms of forcing them to stop their business activities, causing a loss of 90% of their group assets, and almost eliminating all investments during the war. The business group members faced less severe asset losses but income losses were still high due to a severe narrowing of their livelihood options during the war. This also resulted in a very severe food insecurity situation for most of the members. During the war, most (87.5%) of the youth group members were forced to temporarily migrate. The most encouraging finding was that by the time we carried out our postwar survey (August-November 2023), about 80% of the business groups have restarted their group activities by meeting regularly and planning to restart their joint production activities. Most of the members were optimistic that the youth business groups would become an important source of future livelihood for them. This represents strong evidence that resource-poor youth with limited education have the potential and capacity to self-organize and build business activities provided they have the motivation and institutional backing in terms of the provision of resources, adequate guidance and regulation, and the market opportunities are there.
hdl:11250/3166553
Keywords: D74; L1; Q1; Q2; R2; 330; War impacts; Rural youth business groups; Livelihood opportunities; Income; Investment; Food Insecurity; Tigray; Ethiopia